Ergosterol Concentration of Several Different Saccharomyces cerevisiae Yeast Strains - Strydom, Maryke; Kirschbaum, Adrienne F.; Tromp, A. (South African Journal of Enology and Viticulture, 2017)
Differences in the formation of ergosterol in yeast cells have been found amongst several wine yeast strains used in South Africa. A higher ergosterol content is generally accompanied by a faster fermentation rate and results in a shortening of fermentation time. A high ergosterol concentration in the cell is not a prerequisite for maximal cell formation, but probably affects the metabolic activity of the cell. Aeration of the must during the yeast proliferation stage, brought about marked increases in ergosterol concentrations.